Arthroscopically Assisted Retrograde Intramedullary Nailing for Periprosthetic Fracture of the Femur after Posterior-Stabilized Total Knee Arthroplasty - Kazuhiko Udagawa; Yasuo Niki; Kengo Harato; Shu Kobayashi; So Nomoto (Case Reports in Orthopedics)
Retrograde intramedullary nailing (RIMN) has been used for periprosthetic fracture of the distal femur after total knee arthroplasty (TKA), yielding good fracture union rates and satisfactory outcomes. However, RIMN for posterior-stabilized- (PS-) TKA risks malpositioning the entry point and disturbing the post of the tibial insert, and the surgeon therefore usually requires knee joint arthrotomy. We report a case of a 79-year-old male who was involved in bicycle accident resulting in periprosthetic fracture of the distal femur after PS-TKA. We performed osteosynthesis with arthroscopically assisted RIMN to define an appropriate entry point. RIMN for posterior-stabilized- (PS-) TKA risks malpositioning the entry point and disturbing the post of the tibial insert. Because arthroscopy can directly visualize the entry point and the tibial post without arthrotomy, arthroscopically assisted RIMN offers a useful technical option for periprosthetic fracture of the distal femur after PS-TKA.